Real time noninvasive monitoring of contaminating bacteria in a soft tissue implant infection model. - Engelsman, A; van der Mei, H; Francis, K; Busscher, H; Ploeg, R; Dam, v (2009)
Infection is the main cause of biomaterials-related failure. A simple technique to test in-vivo new antimicrobial and/or nonadhesive implant coatings is unavailable. Current in vitro methods for studying bacterial adhesion and growth on biomaterial surfaces lack the influence of the host immune system. Most in vivo methods to study biomaterials-related infections routinely involve implant-removal, preventing comprehensive longitudinal monitoring. In vivo imaging circumvents these drawbacks and is based on the use of noninvasive optical imaging of bioluminescent bacteria. Staphylococcus aureus Xen29 is genetically modified to be stably bioluminescent, by the introduction of a modified full lux operon onto its chromosome. Surgical meshes with adhering S. aureus Xen29 were implanted in mice and bacterial growth and spread into the surrounding tissue was monitored longitudinally from bioluminescence with a highly sensitive CCD camera. Distinct spatiotemporal bioluminescence patterns, extending beyond the mesh area into surrounding tissues were observed. After 10 days, the number of living organisms isolated from explanted meshes was found to correlate with bioluminescence prior to sacrifice of the animals. Therefore, it is concluded that in vivo imaging using bioluminescent bacteria is ideally suited to study antimicrobial coatings taking into account the host immune system. In addition, longitudinal monitoring of infection in one animal will significantly reduce the number of experiments and animals.